2021
DOI: 10.3390/cancers13112705
|View full text |Cite
|
Sign up to set email alerts
|

CALD1 Modulates Gliomas Progression via Facilitating Tumor Angiogenesis

Abstract: Angiogenesis is more prominent in anaplastic gliomas and glioblastoma (GBM) than that in pilocytic and diffuse gliomas. Caldesmon (CALD1) plays roles in cell adhesion, cytoskeletal organization, and vascularization. However, limited information is available on mechanisms underlying the effect of CALD1 on the microvascular facilitation and architecture in glioma. In this study, we explored the role of CALD1 in gliomas by integrating bulk RNA-seq analysis and single cell RNA-seq analysis. A positive correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Based on these results, MIR100HG regulates the expression of the CALD1 by targeting miR-142-5p. Caldesmon (CALD1) is a cytoskeletal protein that regulates cell morphology and movement through interactions with actin filaments, and is closely related to tumor cell migration, invasion, metastasis and blood vessel formation (Cheng et al, 2021;Yao et al, 2021). Therefore, it has attracted increasing attention of cancer researcher in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, MIR100HG regulates the expression of the CALD1 by targeting miR-142-5p. Caldesmon (CALD1) is a cytoskeletal protein that regulates cell morphology and movement through interactions with actin filaments, and is closely related to tumor cell migration, invasion, metastasis and blood vessel formation (Cheng et al, 2021;Yao et al, 2021). Therefore, it has attracted increasing attention of cancer researcher in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Caldesmon 1 (CALD1) [ 93 ] modulates actin filaments of the cytoskeleton, controlling cell morphology and movement. CALD1 expression is augmented in both neoplastic and vascular cells, and it confers worse clinical outcomes.…”
Section: Signaling Pathways Involved In Neovascularizationmentioning
confidence: 99%
“…A recent study of the mechanisms underlying the effect of l-CaD on microvascular facilitation and architecture in glioma showed that l-CaD is associated with abnormal microvessels in anaplastic astrocytoma and glioblastoma (an aggressive grade IV astrocytoma)[ 60 ]. The mechanism of such action was suggested by biofunction prediction to occur by modulating tumor angiogenesis, as ECs and pericytes were more apparent in the tumor microenvironment of high CALD1 expression samples.…”
Section: Cad Contributes To Tumor Angiogenesismentioning
confidence: 99%
“…The mechanism of such action was suggested by biofunction prediction to occur by modulating tumor angiogenesis, as ECs and pericytes were more apparent in the tumor microenvironment of high CALD1 expression samples. Histological and immunofluorescence examination of tumor tissue showed that CaD was associated with vessel architecture in astrocytoma and glioblastoma[ 60 - 63 ]. In stage III/IV mismatch-proficient CRC, CALD1 was upregulated and associated with angiogenesis, as detected by bioinformatics ‘Weighted gene coexpression network analysis’ (WGCNA)[ 41 ].…”
Section: Cad Contributes To Tumor Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation